Ethical issues in organ donation in cases of brain death: a multidisciplinary analysis - Feitosa, Dirceu Hallefe de Souza; Santana, Alberto Magno Ramos; Botelho, Rayane Martins (JRG Journal of Academic Studies, 2023)
Introduction: Organ donation in cases of brain death is a complex and ethical issue involving medical, religious, cultural, and social considerations. Definitions of brain death, religious beliefs, fairness in organ allocation, and the integrity of the donation process are key points of debate and challenge. Methodology: To achieve this objective, a systematic literature review was conducted, encompassing studies that addressed ethical issues in organ donation within the context of brain death. Academic databases were searched to identify relevant articles discussing medical, religious, cultural, and social aspects related to the topic. Results: The analysis of the literature revealed a variety of perspectives on the ethical issues surrounding organ donation in cases of brain death. Debates arose regarding the definition of brain death, with discrepancies between medical and philosophical approaches. Religious beliefs played a crucial role in organ donation decisions, varying widely among different religious groups. Ensuring fairness in organ allocation proved challenging due to donor shortages and the need for equitable criteria. The integrity of the donation process was emphasized as pivotal to maintaining public trust in the system. Conclusion: In conclusion, the systematic review underscored the complexity of ethical issues surrounding organ donation in cases of brain death. The definition of brain death, religious beliefs, fairness in organ allocation, and the integrity of the donation process are interconnected factors requiring a sensitive and multidisciplinary approach. To promote ethical and altruistic organ donation, it is essential to consider diverse perspectives and strive for a balance between cultural values, religious beliefs, medical necessities, and ethical principles.